Characterisation of bacterial populations in Arctic permafrost soils using bacteriohopanepolyols. (November 2015) - Höfle, Silke T.; Kusch, Stephanie; Talbot, Helen M.; Mollenhauer, Gesine; Zubrzycki, Sebastian; Burghardt, Sophia; Rethemeyer, Janet
Highlights: BHP compositions vary between soil horizons and permafrost structures. Structural diversity correlates with lower pH and higher organic carbon content. BHP results agree with 16S rRNA based community structure. Abstract: Bacteriohopanepolyols (BHPs) are biomarkers providing taxonomically and environmentally diagnostic information. BHPs may help to unravel the composition of bacterial communities residing in recent as well as ancient permafrost soils and sediments and also provide information on associated environmental conditions. However, detailed data on their distribution in the heterogeneous Arctic environment are scarce. The distribution and structural diversity of BHPs were studied in the annually thawing (active) layer of three different sites in the polygonal tundra of the Lena Delta in the Siberian Arctic. Variations between permafrost structures and soil horizons caused by differences in the physical and chemical soil properties were observed. C and N content is significantly correlated with the BHP composition so that the highest BHP concentrations and greatest structural diversity occur in the uppermost organic soil horizons, which consist mainly of fresh or little degraded plant material. Furthermore, statistical analyses reveal that higher abundances of adenosylhopane-type soil marker BHPs are linked to higher soil pH values. Small scale environmental controls on BHP distributions are reflected by amine-functionalised BHPs from methanotrophic bacteria only occurring in the water-saturated, oxygen-depleted polygon centres and by soil marker BHPs, which are significantly more abundant in the well aerated polygon rims than in the centres. In contrast, C-2 methylated BHPs, putative indicators of plant-bacterial interactions, are present in all soil horizons and permafrost structures and their relative distribution is not systematically linked to soil properties. Overall, lipid-based results agree with published 16S rRNA based community structure assessments highlighting the usefulness of BHPs to represent bacterial populations in recent and ancient permafrost soils.